Comparative performance study and advanced exergy analysis of novel vapor compression-absorption integrated refrigeration system. (15th September 2018) - Jain, Vaibhav; Sachdeva, Gulshan; Kachhwaha, S.S.
Highlights: Comparative study of cascaded and novel integrated system is presented. Novel integrated system operates at lower generator temperature of 60 °C than cascaded system. Advanced exergy analysis results of novel integrated system are presented. Component priorities for performance improvement of system are represented by Sanky diagram. 35.2% of total irreversibility can be avoided by improving the efficiency parameters. Abstract: In present work, a novel configuration of vapor compression-absorption integrated refrigeration system (VCAIRS) is analyzed. Unlike previous vapor compression-absorption cascaded refrigeration system (VCACRS), proposed configuration works at lower generator temperature of 60 °C. Thus, allowing the use of low grade waste heat for its operation. The performance of VCAIRS is also compared with the equivalent vapor compression refrigeration system (VCRS) and VCACRS for the same cooling capacity of 100 kW. The comparative study result shows that electrical energy requirement in VCAIRS is 21.4% more as compared to VCACRS but it is still 63% less as compared to the equivalent VCRS. Further, the second law efficiency of VCAIRS, VCACRS and VCRS are determined to be 27.9%, 32.7% and 18.8%, respectively. Thus, both the VCAIRS and VCACRS are energy and exergy efficient configurations; but, VCACRS results in more energy efficient cooling technology in the foreseeable future as it utilizes heat at lower generator temperature as compared to VCACRS. After the comparative performance study, the exergetic performance of VCAIRS is further explored based on the coefficient of structural bonds (CSB) and advanced exergy analysis methods. Highest CSB of 4.39 is obtained for high pressure solution heat exchanger but its overall contribution in total irreversibility rate is merely 0.2%; whereas, the highest contribution of 17.4% in total irreversibility rate is by compressor 1 but CSB value computed for it is merely 1.73. Further, advance exergy analysis results show that 35.2% of total irreversibility rate of VCAIRS can be avoided by improving the efficiency parameter of components of system.